2022
DOI: 10.1002/jez.2646
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet affects autophagy and mitochondrial compartment in rat Harderian gland

Abstract: The Harderian gland (HG) of Rattus norvegicus is an orbital gland secreting lipids that accumulate in excess under condition of increased lipid metabolism. To study the response elicitated by lipid overload in rat HG, we housed the animals in thermoneutral conditions (28−30°C) in association to high fat diet (HFD). In HFD rats alterated blood lipid levels result in lipid accumulation in HG as demonstrated by the increased gland weight and histochemical/ultrastructural analyses. The HFD‐caused oxidative stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…This was in accordance with higher levels of serum cholesterol and triglycerides found in the rats fed with HFD, suggesting that high fat intake induced lipophagy in the corpus of epididymis as a protective response to lipid accumulation. These data are in line with those of our previous study, where we found that the expression of the Perilipin3 protein was higher in the Harderian gland (a lipoprotein gland) of rats following an HFD treatment (Chieffi Baccari et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…This was in accordance with higher levels of serum cholesterol and triglycerides found in the rats fed with HFD, suggesting that high fat intake induced lipophagy in the corpus of epididymis as a protective response to lipid accumulation. These data are in line with those of our previous study, where we found that the expression of the Perilipin3 protein was higher in the Harderian gland (a lipoprotein gland) of rats following an HFD treatment (Chieffi Baccari et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…3 G). These data suggest that mitochondrial DNA copy number does not directly correlate with mtDNA damage [ 35 ] and that mitochondrial biogenesis, fission, and fusion may adjust for any potential loss in mtDNA copy number [ 36 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that the rat HG is located in the medial corner of the orbit, and it is continuously exposed to light, therefore the porphyrins produced can absorb UV light generating ROS via photo-oxidation (Hugo et al, 1987;Spike et al, 1990) 2021) demonstrated that in the hamster HG, autophagy and selective autophagy are activated as a protective response to OS induced by elevated intake of fructose, a nutritional element which plays a fundamental role in the developing disorders associated with metabolic syndrome. Because of this evidence, rodent HG is used as a model to have more insights and a better understanding of OS and its effects (Chieffi Baccari et al, 2022;Coto-Montes & Tomas-Zapico, 2006;Coto-Montes et al, 2001;Kong et al, 2021;Romano et al, 2022;Tomás-Zapico et al, 2005).…”
Section: Resultsmentioning
confidence: 99%